Similar cellular responses after treatment with either praziquantel or oxamniquine in Schistosoma mansoni infection - Mduluza, Takafira (The Medical Association Of Malawi, 2009)
The effect of treatment with either oxamniquine or praziquantel on S.mansoni specific IFN-gamma, IL-4 , IL-5 and IL-10 was compared on PBMC which were collected pretreatment, 6 and 18 weeks post treatment. Using sandwich ELISA on the supernatants harvested from the PBMC stimulation by crude S. mansoni SEA and SWAP antigens after 5 days the levels of PBMC proliferation and cytokine production were similar according to treatment with either praziquantel or oxamniquine. Before treatment, infected groups showed low ratios, of IL-4:IFN-gamma, IL-5:IFN-gamma and IL-10:IFN-gamma, indicating that IFN-gamma was high in the infected individuals. The general increase in immuno-modulation was observed post-treatment with elevated immune reactivity and cytokine production in both treatment groups. Treatment induced significant increases in levels of IL-4 (p<0.05), IL-5 (p<0.0001) and IL-10 (p<0.05) cytokines 6 and 18 weeks after treatment. There were no significant differences in the increase in IL-4, IL-5 and IL-10 between children treated with praziquantel or oxamniquine. Pre-treatment IFN-gamma and IL-5 levels were positively correlated with infection (p<0.001), while post treatment IL-4 cytokine levels were negatively correlated with baseline infection status (p<0.001). The results suggest that treatment-induced immune responses are similar for both commonantischistosome drugs praziquantel or oxamniquine having similar and immunizing effect.